A novel in vivo test method for evaluating the infrared radiation protection provided by sunscreen products. Issue 6 (23rd July 2019) - Kim, Su Ji; Bae, Jiyoun; Lee, Sung Eun; Lee, Jun Bae; Park, Chun Ho; Lim, Doo Hyeon; Park, Myeong Sam; Ha, Jaehyoun
Abstract: Background: Infrared radiation (IR) exposure generates reactive oxygen species and induces matrix metalloproteinase‐1 expression in human skin. Moreover, while not as acute as ultraviolet radiation, repeated infrared irradiation can result in the photoaging of skin. Broad‐spectrum sunscreens can protect skin from IR, but no human in vivo test methods for the evaluation of sunscreens' IR protection effect have been developed. We aimed to develop such a method. Materials and Methods: We included 155 Korean subjects in our three‐part clinical study. The IR reflectance of subjects' skin was measured using a benchtop model of an IR light source and a reflectance measuring probe. We measured the IR reflectance in relation to skin color and hydration level to set up our experimental conditions. We then calculated the infrared protection factors (IPFs) of cosmetic emulsions as the IR reflectance ratio between cosmetic sunscreen‐applied skin and non‐sunscreen‐applied skin and assessed the relationship between IPFs and the amount of sunscreen ingredients. Finally, this method was validated using several commercial sunscreen cosmetics. Results: Skin color and hydration level did not influence the IR reflectance of subjects' skin. The IPFs of cosmetic sunscreens showed a positive correlation with the amount of inorganic sunscreen ingredients. Conclusion: In this study, we developed a simple, fast, and ethically acceptable human in vivo test method for evaluating the IPFs of cosmetic sunscreens.